Analisis Konsep Wasiat Wajibah dalam KHI dan Putusan MA - Gafur, Abdul (UIN Sunan Kalijaga Yogyakarta, 2022)
This article attempts to answer two questions regarding the concept of wasiat wajibah: first, what is the background of KHI Article 209 concerning wasiat wajibah and the reason of Supreme Court extends the concept of wasiat wajibah to non-Muslim relatives and stepchildren; second, how are the similarities and differences between wasiat wajibah in the KHI and the Supreme Court's decision. This article is a qualitative research using data sourced from the literature. The data obtained then analyzed using a descriptive-comparative approach. The results of the discussion shows that wasiat wajibah in the KHI is motivated by Islamic law, customary law and in order to provide legal certainty and bridging legal differences between Islamic law and customary law related to adoption law. As for the wasiat wajibah in the Supreme Court Decision, which is given to non-muslim relatives to fill a legal vacuum, on the basis that judges may not reject cases that have no law or are unclear. The difference between wasiat wajibah in the KHI and the Supreme Court's decision is in terms of the recipient of wasiat wajibah. According to KHI, it is intended for adopted children and adoptive parents with a maximum of 1/3 of the inheritance. Meanwhile, the Supreme Court's decision can be applied to non-muslim relatives and stepchildren. They get a share of muslim heirs based on wasiat wajibah as much as the share of muslim heirs on an equal footing, a maximum of one third or a maximum of 1/3 of the inheritance.